Kualitas Pengajar dan Hubungannya dengan Kepuasan Mahasiswa di Sekolah Tinggi Pariwisata X - Subekti, Kukuh Galih (Binus Business Review, 2010)
Educational institution as a provider of skilled manpower in the tourism industry is the focus of the research field of tourism. Education was instrumental in creating quality human resources. Education in the teaching process can be interpreted as a process of creating a quality resource. Today many emerging institutions or educational institutions have a similar goal, promoting competition in terms of absorption of students with the advanced system of teaching, facilities and quality teachers. Students as customers of the educational institution require the services here in the form of reciprocal teaching with payments to educational institutions. Students can stay in one educational institution if the service of educational institutions provides benefits to student functions.Â